THE ISSUE OF OBSERVANCE OF SAFE FOLLOWING DISTANCE BETWEEN VEHICLES IN GERMANY - Zemanek, Lukas; Prnka, Jiri (European Scientific Journal, ESJ, 2015)
This technical article discusses the issue of observance of safe following distance between vehicles on motorways in the Federal Republic of Germany. It contains an analysis of accident frequency on roads in Germany, with a particular focus on traffic accidents caused by the failure to observe a safe following distance behind another vehicle. Next, it describes legal requirements on the observance of a safe distance in particular countries and, in respect thereof, it presents results of an analysis of the observance of a safe following distance between vehicles on German motorways containing two and three traffic lanes per carriageway in one direction.